Study on Evaluation and Prediction of the Degree of Surface Damage Caused by Coal Mining - Xie, Xiaoshen; Hou, Enke; Long, Tianwen; Feng, Dong; Hou, Pengfei; Wei, Qiming; Li, Yang; Liu, Jiangbin (Frontiers in Earth Science, 2022)
Surface damage caused by coal mining is one of the problems perplexing ecological environment restorations in coal mining areas. Accurately evaluating and predicting the degree of surface damage induced by coal mining with reasonable and correct indexes are of great significance to the restoration and treatment of the ecological environment. In this paper, these methods including the unmanned aerial vehicle aerial photography and manual measurement were used to investigate the development characteristics of surface damage caused by 2# coal seam mining in Yangchangwan Coal Mine. The results showed that with the change of mining conditions, the characteristics of surface cracks change obviously, which can be adopted to indicate the degree of surface damage. Thus, based on the results of the investigation, the classification standard of surface damage degree was established based on the evaluation indexes including density of crack, drop height of surface crack, crack width, maximum surface subsidence, and geological disaster caused by cracks and the damage characteristics of buildings. The evaluation method and process of surface damage degree also were given. Based on the ratio of the buried depth to the thickness of the coal seam (H/M), ratio of the thickness of overlying bedrock to the thickness of the coal seam, the thickness of loose layers (Ms), geomorphology, distance to faults, and distance to folds, the prediction model of surface damage degree was built on the GIS platform. The weight coefficient of each prediction index was obtained by the analytic hierarchy process (AHP) method. The surface damage degree map of 2# coal seam in Yangchangwan Coal Mine was divided into four classes: very minor, minor, moderate, and serious, which provides a relatively applicable method for the prediction of surface damage degree in Yangchangwan Coal Mine and its adjacent mining areas.